Decision Analysis of Offshore Channel Maintenance Dredging in PT. PQR - Gangga, Rahadhian Adhitya; Novani, Santi (International Journal Labs, 2023)
The offshore channel maintenance dredging completion date, which was performed by PT. ABC (PT. PQR’s contractor) using crane barge XYZ, was delayed to 19 May 2023 (43.4 days delayed). Two main problem were identified using Kepner Tregoe Situation Analysis (KT-SA) based on the company data processing and one most main contributing problem (lack of daily sediment production; the initial plan was 1500 m3/day) then be analyzed using Kepner Tregoe Problem Analysis (KT-PA) and the root cause was constructed using cause-map with brainstorming method included in the process between author and some of PT. ABC dredging crew in crane barge XYZ. Substitute, Combine, Adapt, Modify, Put on another use, Eliminate, Rearrange (SCAMPER) technique then be brought in the brainstorming session with PT. ABC dredging crew on crane barge ABC to bring alternative solutions for the root cause of the problem. Furthermore, the SCAMPER result be brought to brainstorming with PT. PQR dredging operation assistant manager, as the problem holder and matter expert, and filtered to three most possible alternative solutions. These three most possible solutions then examined using Simple Multiple Attribute Rating Technique (SMART) method with eight stages were performed. The criteria used in this method are offshore channel dredging project cost, offshore channel dredging project schedule, coordination with other entity, and permit to work (PTW) & derogation. The objectives of this research are knowing what factors affecting the dredging project in PT. PQR offshore channel case and the alternative solution to be brought in the next offshore channel maintenance dredging.